Implikasi Perbedaan Klasifikasi AWaRe WHO Dan Kemenkes RI Terhadap Evaluasi Penggunaan Antibiotik: Tinjauan Literatur - Yusna Fadliyyah Apriyanti; Reza Rahmawati; Muthia Nurhidayah; Baha Udin (Poltekkes Kemenkes Bengkulu, 2026)
The AWaRe classification was developed by the WHO to support antimicrobial stewardship through standardized evaluation of antibiotic use. Several countries, including Indonesia, have implemented AWaRe classifications adapted to national clinical needs and policy priorities, although such adaptations may lead to variations in the interpretation of antibiotic use indicators and stewardship performance. A literature search was conducted using the Google Scholar database with the keywords “AWaRe classification”, “antibiotic use evaluation”, “WHO”, and “Indonesia”, accompanied by the addition of the affixes